Gender-Based Violence: Perspectives from Africa, the Middle East, and India - Djamba, Yanyi K (Springer, 2015)
This book offers new perspectives on gender-based violence in three regions where the subject has been taboo in everyday discourse often due to patriarchal cultural norms that limit women’s autonomy. The contributions to this book provide rare insight into not only the levels and the socio-demographic determinants of domestic violence, but topics ranging from men’s attitudes toward wife beating; domestic violence-related adolescent deaths, and women’s health problems due to sexual and physical abuse. With a comprehensive introduction that provides a comparative international research framework for discussing gender-based violence in these three unique regions, this volume provides a key basis for understanding gender-based violence on a more global level.